Från litteraturförståelse till literacy - Borsgård, Gustav; Jönsson, Maria (Tidskrift för litteraturvetenskap, 2019)
From Literary Comprehension to Literacy: The Expansion of a Concept and its Consequences for the Teaching of Literature During the last few decades, the concept of ”literacy” has had a growing impact on the vast fields of education. Although the uses of the concept are multifaceted and diverse, the hegemonic policy discourse as supported by the OECD treats literacy as an individual competence closely tied to the development of explicit reading strategies. This article examines what the concept of literacy means for literary studies in general and literature education in particular. We argue that there are reasons to critically reflect upon the effects of invoking the concept of literacy in the field of literature education. With the aid of theorists like Rita Felski and Toril Moi, our main focus is to examine the risks of centering attention on the ”subject” (the student and his/her abilities) instead of the ”object” (in our case, the works of fiction). By turning to Gert Biesta and Emmanuel Lévinas, we argue that there is an educational value in acknowledging and appreciating what lies beyond the scope of the student’s immediate understanding.